Genomic and in-vitro characteristics of a novel strain Lacticaseibacillus chiayiensis AACE3 isolated from fermented blueberry - Li, Xin-Dong; Lin, Yi-Cen; Yang, Rui-Si; Kang, Xin; Xin, Wei-Gang; Wang, Feng; Zhang, Qi-Lin; Zhang, Wen-Ping; Lin, Lian-Bing (Frontiers in Microbiology, 2023)
Numerous different species of LAB are used in different fields due to their unique characteristics. However, Lacticaseibacillus chiayiensis, a newly established species in 2018, has limited microorganism resources, and lacks comprehensive evaluations of its properties. In this study, L. chiayiensis AACE3, isolated from fermented blueberry, was evaluated by genomic analysis and in vitro assays of the properties. The genome identified genes associated with biofilm formation (luxS, ccpA, brpA), resistance to oxidative stress (tpx, trxA, trxB, hslO), tolerance to acidic conditions (dltA, dltC), resistance to unfavorable osmotic pressure (opuBB, gbuA, gbuB, gbuC), and adhesion (luxS, dltA, dltC). The AACE3 showed 112 unique genes, relative to the other three L. chiayiensis strains. Among them, the presence of genes such as clpP, pepO, and feoA suggests a possible advantage of AACE3 over other L. chiayiensis in terms of environmental adaptation. In vitro evaluation of the properties revealed that AACE3 had robust antibacterial activity against eight common pathogens: Streptococcus agalactiae, Staphylococcus aureus, Escherichia coli, Salmonella enteritidis, Salmonella choleraesuis, Shigella flexneri, Pseudomonas aeruginosa, and Klebsiella pneumoniae. In addition, AACE3 showed more than 80% survival rate in all tests simulating gastrointestinal fluid, and it exhibited high antioxidant capacity. Interestingly, the cell culture supernatant was superior to intact organisms and ultrasonically crushed bacterial extracts in all tests of antioxidant capacity. These results suggested that the antioxidant capacity may originate from certain metabolites and extracellular enzymes produced by AACE3. Moreover, AACE3 was a moderate biofilm producer due to the self-agglomeration effect. Taken together, L. chiayiensis AACE3 appears to be a candidate strain for combating the growing incidence of pathogen infections and antioxidant production.